The battle to secure our public access computers. - Sendze M (Computers in Libraries, 2006)
There's a plethora of computer network enemies these days, so there's a constant battle to protect a system's confidentiality, integrity, and accessibility. You can share this battle plan, which has been deployed at one public library system in Kansas.